Nuclear magnetic resonance for the differentiation of benign and malignant breast tissues and axillary lymph nodes. - Fossel, E T (1983)
We have utilized proton T1 (spin-lattice relaxation time) values of Nuclear Magnetic Resonance to study 110 tissue samples obtained from 11 mastectomy specimens. Samples of 1 cm3 from primary tumor sites, nipples, and other breast quadrants, as well as intact lymph nodes were studied and then histologically scored for the presence or absence of carcinoma and, if present, whether it was an isolated microscopic focus (micro). Of 54 samples of breast tissue, 12 contained carcinoma, 5 micro: of 45 lymph nodes, 15 contained metastatic carcinoma, 2 micro; of the 11 nipples, 2 had carcinoma, both micro. For the malignant samples (excluding micro) mean T1 value was 0.47 +/- 0.07 sec, (range 0.39-0.79 sec). For the 72 benign samples (excluding nipple) mean T1 value was 0.26 +/- 0.03 sec (range 0.14-0.36 sec). The 13 tumor-bearing nodes had a mean T1 value of 0.47 +/- 0.03 sec (range 0.40-0.63 sec); mean for the benign nodes was 0.26 +/- 0.007 sec (range 0.19-0.35 sec). The differences were highly significant in each case (p less than 0.001). For micro examples, T1 values were at malignancy threshold levels or just below, except for nipple tissues, where discrimination was poor. For the 20 other malignant samples, there was no correlation between T1 value and the per cent of sample containing malignancy.